Repeated Reading Technique and Its Role in Enhancing Students’ Reading Comprehension - Yokbeth Sirwa; Nursalim (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
This study investigates the effect of the repeated reading technique on students’ reading comprehension at the tenth grade of MA Muhammadiyah Aimas during the 2021/2022 academic year. The research used a pre-experimental design with one group receiving a pre-test and post-test. The participants consisted of 10 students selected through purposive sampling. Data were collected using a multiple-choice reading comprehension test and analyzed quantitatively using descriptive statistics and a normalized gain (N-Gain) formula. The results showed that the students’ mean score increased from 36.00 in the pre-test to 72.50 in the post-test, with an N-Gain score of 57.03%, indicating a “quite effective” category. These findings suggest that repeated reading helps students improve their understanding of descriptive texts by increasing their reading fluency and comprehension accuracy. The study concludes that repeated reading is an effective technique for teaching reading comprehension and recommends its use as an alternative strategy in English classrooms.